Ghana's Debt Crisis and the Political Economy of Financial Dependence in Africa : History Repeating Itself? - Akolgo, Isaac Abotebuno (Development and Change, 2023)
Recent accounts of the re-emergence of debt distress in Africa, while offering significant insights, fail to provide the historical political-economic context within which African indebtedness is set. On the surface, spending induced by the COVID-19 pandemic, economic fallout from the Russia–Ukraine war, and repeated examples of fiscal indiscipline by African governments appear to be the causes of the current wave of debt crises. Beyond these factors, however, this article argues that the present indebtedness, like previous episodes, is rooted in the economic and financial subordination of African economies. Specifically, the article places Ghana's extensive debt within the country's post-independence political-economic context, and thus traces the structural factors and external constraints that underlie its economic vulnerability and financial dependence. These include the collapse of developmentalism in the 1970s, the Structural Adjustment Programmes of the 1980s, and an exploitative transnational lending system dominated by Western commercial creditors. Internally, recent fiscal mistakes by the government, within its limited policy space, have exacerbated Ghana's indebtedness. The Ghanaian experience shows that unconditional debt cancellation, widely called for, is a necessary but insufficient measure to address the recurring cycles of indebtedness. Debt cancellation should be followed by broader economic and financial reforms, globally and domestically.